CONTEXTUALIZATION OF HADITH AND MULTICULTURAL QUR'ANIC VERSES IN EDUCATION - Khumaidi, Ahmad; Yahya, Kustiana (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Diversity is not something new, especially in Indonesia. This country, which was built on cultural, ethnic and cultural diversity, makes Bhineka Tunggal Ika the nation's identity to embrace these differences, especially in the world of education which is then known as multicultural education. This research is important to study, apart from the conditions in Indonesia which is inhabited by various cultures, the Qur'an and Hadith are also the main sources of jurisprudence to underlie multicultural education. Therefore, this research uses al-Qur'an and hadith as the main data in this research, so this research uses library research. In the end, this study explains multicultural education, including through the verses of the Qur'an QS. Al- Baqoroh: 62, QS. Ar-Rum: 22, QS. Al-Hujurot: 13 and QS. Yunus 40-41 and the hadith narrated by Imam Bukhori and Ahmad bin Hambal. In the Qur'an it is explained that the differences in religions, culture and ethnicity are not something that should be a problem, because basically the standard for measuring someone is their piety. While the perspective of the hadith is tolerance as one form of respecting differences in a multicultural culture.